PENGARUH RETRIBUSI DAERAH, HASIL PENGELOLAAN KEKAYAAN DAERAH YANG DIPISAHKAN, DAN LAIN-LAIN PENDAPATAN ASLI DAERAH YANG SAH TERHADAP PENDAPATAN ASLI DAERAH JAWA TENGAH PERIODE 2021-2023 - Melindawati, Clara Putri; Kurniawati, Lintang (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study uses Regional Retribution, Separate Regional Wealth Management Income, Other Legitimate Regional Income to see how the three variables affect the Regional Original Income off all Regencies/Cities in Central Java for the 2021-2023 period. Methods: Descriptive Statistical Tests, Classical Assumption Tests, and Multiple Linear Regression Analysis uses to analyze the influence between variables using SPSS analysis statistics because this study is a quantitative study.Results: The results indicate that Regional Retribution does not significantly and negatively affect Revenue Original Income, Separated Regional Wealth Management Income significantly and negatively affects Regional Original Income, and Other Legitimate Regional Income does not significantly and negatively affect Regional Original Income.Conclusion and suggestion: The increase in revenue from Separated Regional Wealth Management Income has not been able to maximize Regional Original Income. In addition, the less than optimal revenue from Regional Retribution and Other Legitimate Regional Income has not been able to drive an increase in Regional Original Income. This is influenced by other variables that can increase Regional Original Income, such as 8.6% of the determination coefficient (R2), can be interpreted ad independent variabeles in the study affecting Regional Original Income by 8,6%, while other factors affect 91.4%. The scope of the next study must be expanded, use a longer period, and other variables such as Regional Tax can be added for more accurate results. Keywords: Legitimate Regional Original Revenue, Regional Original Revenue, Regional Retribution, Revenue from the Management of Separated Regional Assets